Analysis of the Papal Benediction Sign: The ulnar neuropathy of St. Peter. Issue 6 (28th June 2015) - Futterman, Bennett
<x xml:space="preserve">Abstract</x> The origin of the Papal Benediction Sign has been a source of controversy for many generations of medical students. The question has been whether the Papal Benediction Sign posture is the result of an injury to the median nerve or to the ulnar nerve. The increasingly popular use of online "chat rooms" and the vast quantities of information available on the internet has led to an increasing level of confusion. Looking in major anatomy texts, anatomy and board review books as well as numerous internet sites the answer remains unresolved. Through the analysis of functional anatomy of the hand, cultural and religious practices of the early centuries of the Common Era and church art a clear answer emerges. It will become apparent that this hand posture results from an ulnar neuropathy. Clin. Anat. 28:696–701, 2015. © 2015 Wiley Periodicals, Inc.